Por uma verdadeira participação dos trabalhadores: o caso da Flaskô: fábrica sob controle operário - Dimitri Augusto da Cunha Toledo (2011)
The experiences of the occupied companies are inserted in the search for the jobs maintenance and the labor laws of the laborers. In these experiences the workers manage the production means, through the Laboring Control. In this process, the workers organize themselves in committees, in order to manage the organization, from the installation of a democratic and participative environment form those can contribute in the in the decision process, as much as in the vote process, and in the spheres of importance of the decision process. These organizations keep its bases fixed in emancipation principles and politics resistance, beyond the combat for the autonomy. Its important to stand out that, they emphasize the alternative forms of management, its organizational model, over all those that wish for bigger participation and decentralization of the decision processes. Thus, the proposal of this paper is to study an occupied company managed by the laborers: the Flaskô. The Flaskô Industrial de Embalagens Ltda is an industry of plastic transformation of the sector of packing. The plant produces bombonas mainly, big drums with the capacity of about two hundred liters, used for storage of foods, chemical cosmetics, agro toxics, products, seasonings, etc. The occupation of the company for its workers happened in June 12th 2003, and, since then, it comes being controlled for the Company Advice that is elect for all the employees, in assembly. About sixty -five workers of the company keep the production and promote a campaign continued for the nationalization of the company. Through this, this paper will analyze the participation of the workers in a occupied company under laboring control. For this, it was used of different categories of analysis. These categories had served to assist in the understanding of as if it inside gave the process of participation of the Flaskô. The intention was of if analyzing in not linear way to the organization forms/management diligent them of the Flaskô. This process was made basically from a participant comment of the daily one of the laborers. Still in the methodological aspect they had been used as technique of associated collection of data to the following techniques: documentary, half-structuralized interview, daily analysis of field, beyond already said participant comment. On the basis of all these information to the end of this work, can be said that the practical ones of organization in a busy plant under laboring control make possible a bigger participation of the workers. Specifically the Flaskô, that is the studied case, considers a collective management that brings the workers for the process of taking of decision. One notices that to study organizations as the Flaskô contributes with thinking and rethink of practical alternatives of organizations. One expects that the decurrently results of this work contribute with studies of organizations that establish practical alternatives of organization, with the movement of busy plants, the management of these plants, with the constant concern with the participation level. And from this study a new reflection emerges.